Short-range correlations seen in the nematic phase of bent-core liquid crystals by dielectric and electro-optic studies - VIJ, JAGDISH; JANG, YUN; PANOV, VITALI; KOCOT, ANTONI (My University, 2011)
Three bent-core nematic liquid crystals having the same core but with different terminal groups, short (C4) and long (C7,C9) tails, are investigated by dielectric and electro-optic contrast spectroscopic techniques. C4 shows sign reversal in the dielectric anisotropy ??? as a function of both temperature and frequency, whereas C9 shows only negative ??? in the entire mesophasic region. The behavior of C7 is intermediate of the two. Results of a dielectric study show that both C7 and C9 exhibit strong short-range polar correlations normal to the director. The correlation lengths of these interactions are found to be similar to those from the x-ray scattering. An increased hindered rotation for C9 compared to C4 moves the dielectric dispersion for ??? to much lower frequencies, such that C9 shows only negative ??? over the entire temperature range.
PUBLISHED
Keywords: Optics; bent-core liquid crystals; dielectric; electro-optic; Nanoscience & Materials